Social determinants of health: A pedagogical framework for advancing the Citizen Scholar. (November 2018) - Velardo, Stefania
The concept of the Citizen Scholar highlights the potential for universities to act as vehicles for social change by supporting the development of active, engaged graduates who are geared to respond to current and future global challenges. This demands a radical shift in teaching towards more interactive pedagogies, which may prove difficult for some educators and students who are comfortable with a traditional model of learning and 'teaching to the test'. Despite these challenges, universities have a responsibility to bring about change in practice to prepare undergraduate students for the complex outside world. This article reports on a revised version of a 12-week Australian undergraduate course in health promotion that was delivered to 147 first-year students enrolled in a Bachelor of Education and/or Bachelor of Health Sciences degree. Significant revisions were made to the curriculum and modification of teaching methodology, with the aim of encouraging greater social awareness and students' capacity for social change. In this article, I reflect on various teaching strategies employed to develop skills and proficiencies akin to the Citizen Scholar, with a particular emphasis on fostering critically health literate graduates who are empowered to create healthy, just societies. Strategies included the facilitation of discussions to ignite empathy, integrating problem-solving activities and building advocacy competencies. A collaborative, learner-directed approach is considered as a way forward for other university educators, as a way of disrupting previous pedagogic work that emphasises knowing 'about' social problems rather than 'acting on' them.